The Assistance in Indonesian Language Learning at Muang Nakhon Si Tammarat School, Thailand through Contextual Learning - Kadek Ari Andini; Putu Beny Pradnyana (The Future of Education Journal, 2025)
This study aims to analyze the effectiveness of implementing the Contextual Teaching and Learning (CTL) approach in assisting Indonesian language learning for Thai students at Muang Nakhon Si Tammarat School. The study employs a descriptive qualitative approach conducted through observation, interviews, and documentation during the learning activities. CTL was implemented by linking language materials to students’ real-life contexts, using visual media, contextual dialogues, and interactive learning activities. The results indicate that CTL is able to improve students’ linguistic abilities, particularly in mastering basic vocabulary and constructing simple sentences. Students found it easier to understand word meanings because the learning process was based on direct experience and visual associations. The application of CTL also had a significant impact on students’ activeness and confidence in communication. A communicative classroom atmosphere and relevant activities encouraged students to speak more confidently, even when using simple sentence structures. In addition, visual media such as pictures, word cards, and PowerPoint presentations were proven to strengthen students’ retention and understanding of Indonesian language and cultural concepts. The study also found that CTL contributed positively to students’ learning attitudes and motivation, as indicated by increased enthusiasm, curiosity, and participation in interactive activities. Although there were challenges, such as phonological differences and limited time, these obstacles could be addressed through repetitive practice, the use of audio media, and scaffolding according to students’ needs. Overall, this study concludes that CTL is an effective and applicable approach for teaching Indonesian to beginners in a cross-cultural context.